2020
DOI: 10.1016/j.biopsych.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Modification of Fatty Acid Amide Hydrolase Messenger RNA in Circular RNA STAG1–Regulated Astrocyte Dysfunction and Depressive-like Behaviors

Abstract: BACKGROUND: N 6-methyladenosine (m 6 A) is the most abundant epigenetic modification in eukaryotic messenger RNAs and is essential for multiple RNA processing events in physiological and pathological processes. However, precisely how m 6 A methylation is involved in major depressive disorder (MDD) is not fully understood. METHODS: Circular RNA STAG1 (circSTAG1) was screened from the hippocampus of chronic unpredictable stresstreated mice using high-throughput RNA sequencing. Microinjection of circSTAG1 lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 40 publications
(74 reference statements)
1
96
1
Order By: Relevance
“…Huang et al showed that circSTAG1 overexpression inhibited the ALKBH5 translocation into the nucleus, leading to an increased m6A methylation of FAAH mRNA and its degradation in astrocytes. This in turn determined an improvement of astrocyte functionality and a reduction of depressive-like behaviors induced by CUS [90].…”
Section: M6a Rna Modificationmentioning
confidence: 93%
“…Huang et al showed that circSTAG1 overexpression inhibited the ALKBH5 translocation into the nucleus, leading to an increased m6A methylation of FAAH mRNA and its degradation in astrocytes. This in turn determined an improvement of astrocyte functionality and a reduction of depressive-like behaviors induced by CUS [90].…”
Section: M6a Rna Modificationmentioning
confidence: 93%
“…Methylated RNA immunoprecipitation sequence analysis in the peripheral blood found that circSTAG1 is significantly reduced in chronic unpredictable mild stress (CUMS) mice and MDD patients. On the contrary, overexpression of circSTAG1 induced a positive effect on CUMS-induced astrocyte dysfunction and depression-like behavior (Huang et al, 2020). With the same detection method, the methylation level of the serotonin 1-A receptor (5-HT1A) promoter was found to be closely related to mRNA transcription and protein expression, the presence of stress increased the level of 5-HT1A mRNA in the prefrontal cortex of CUMS mice by 50%.…”
Section: Chronic Unpredictable Mild Stress Affects Methylationmentioning
confidence: 97%
“…Additionally, circFOXP1 promotes the Warburg effect and gallbladder progression by increasing the cytoplasmic translocation of PTBP1 that binds to the 3′-UTR and coding region of pyruvate kinase L/R (PKLR) mRNA, protecting it from decay [ 138 ]. Similarly, circSTAG1 ameliorated astrocyte dysfunction and depressive-like behaviors induced by chronic unpredictable stress by capturing ALKBH5 in the cytoplasm and increasing m6A levels of fatty acid amide hydrolase (FAAH) mRNA [ 139 , 166 ]. CircBACH1 [ 140 ] and circZFP609 [ 141 ] also fall in this situation.…”
Section: Circrna-protein Interactionsmentioning
confidence: 99%